1983
DOI: 10.1111/j.1440-0960.1983.tb00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans Cell and Melanocyte Distribution in “Normal” Human Epidermis

Abstract: Langerhans cells and melanocyte distribution was determined in 18 different body sites in 76 cadavers, 44 men and 32 wotnen, within 24 hours of death. The Langerhans cell and melanocyte counts were inversely related so that in sun-exposed (tanned) epidermis Langerhans cell number.^ were lower and melanocyte numbers were higher than in nott-exposed (non-tanned) epidertnis. Langerhatis cell atid tnelatwcyte densities were sitnilar in tnen and wottien on non-exposed (non-tanned) epidertnis when matched by age. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…Our studies confirm that greater numbers of cells are labelled with anti-OKT6 than with anti-HLA-DR. Certain reservations have been expressed regarding the reliability of the ATPase stain for Langerhans cell detection, since melanocytes may also be stained by this technique (Nordlund and Ackles, 1981), although to a lesser degree than Langerhans cells. Since comparable numbers of Langerhans cells were detected with either ATPase or OKT6 antibody in this study, we must concur with Scheibner et al (1983) that, at least in experienced hands, ATPase staining is an acceptable method for Langerhans cell quantitation, although it is certainly more subject to interpretive errors.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our studies confirm that greater numbers of cells are labelled with anti-OKT6 than with anti-HLA-DR. Certain reservations have been expressed regarding the reliability of the ATPase stain for Langerhans cell detection, since melanocytes may also be stained by this technique (Nordlund and Ackles, 1981), although to a lesser degree than Langerhans cells. Since comparable numbers of Langerhans cells were detected with either ATPase or OKT6 antibody in this study, we must concur with Scheibner et al (1983) that, at least in experienced hands, ATPase staining is an acceptable method for Langerhans cell quantitation, although it is certainly more subject to interpretive errors.…”
Section: Discussionsupporting
confidence: 74%
“…Our finding of lower numbers and the earlier disappearance of Langerhans cells in neonatal explants may have been due to differences in the maturity and site of origin of the tissue used. Scheibner et al (1983) have reported that Langerhans cell density in genital epidermis is lower than that in other body sites.…”
Section: Discussionmentioning
confidence: 94%
“…7 Although Whiteman and colleagues 8 speculated that these differences could be predetermined, other authors attribute much of the difference to the effects of sun exposure. [9][10][11][12][13][14] The precise magnitude of the effect is not certain, but one study reported up to a twofold increase in melanocyte density in sun-exposed skin compared with shielded skin. 9 Unexpectedly, our study showed a relative diminutive melanocyte density for the eyebrow and eyelid (Q11.75 and Q11.0, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The increased melanin content in the keratinocytes causes the brown coloured 'sun tan' (15). The number density of melanocytes in the human body is thought to be similar in people of all races, but the number of active epidermal melanin units varies in the different regions of the body (16). Furthermore, sunlight acutely increases the melanocyte population, while cold or severe thermal burns decrease the number of pigment cells in affected skin, presumably due to the inflammatory/immune process.…”
Section: Epidermis: Functional Structurementioning
confidence: 99%
“…The total temperature rise in the single melanosome, with radius m, results from heat produced in the melanosome itself [Equation 12 in Svaasand et al (27)] and heat diffusing from the neighbouring melanosomes [Equation 16 in Svaasand et al (27)]. Damage occurs when the sum of these contributions bring the temperature rise above the threshold of 80~ The corresponding threshold energy, Qth, is then found for the single melanosomes.…”
Section: Lt Norvang Te Milner Js Nelson Et Almentioning
confidence: 99%